Radiation dose verification using real tissue phantom in modern radiotherapy techniques - Gurjar, Om Prakash (Medknow Publications & Media Pvt Ltd, 2014)
In vitro dosimetric verification prior to patient treatment has a key role in accurate and precision radiotherapy treatment delivery. Most of commercially available dosimetric phantoms have almost homogeneous density throughout their volume, while real interior of patient body has variable and varying densities inside. In this study an attempt has been made to verify the physical dosimetry in actual human body scenario by using goat head as “head phantom” and goat meat as “tissue phantom”. The mean percentage variation between planned and measured doses was found to be 2.48 (standard deviation (SD): 0.74), 2.36 (SD: 0.77), 3.62 (SD: 1.05), and 3.31 (SD: 0.78) for three-dimensional conformal radiotherapy (3DCRT) (head phantom), intensity modulated radiotherapy (IMRT; head phantom), 3DCRT (tissue phantom), and IMRT (tissue phantom), respectively. Although percentage variations in case of head phantom were within tolerance limit (< ± 3%), but still it is higher than the results obtained by using commercially available phantoms. And the percentage variations in most of cases of tissue phantom were out of tolerance limit. On the basis of these preliminary results it is logical and rational to develop radiation dosimetry methods based on real human body and also to develop an artificial phantom which should truly represent the interior of human body.